2022
DOI: 10.1007/s00203-022-02957-z
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species accumulation is synchronised with growth inhibition of temperature-sensitive recAts polA Escherichia coli

Abstract: When combined with recombinase defects, chromosome breakage and double-strand break repair deficiencies render cells inviable. However, cells are viable when an SOS response occurs in recAts polA cells in Escherichia coli. Here, we aimed to elucidate the underlying mechanisms of this process. Transposon mutagenesis revealed that the hslO gene, a redox chaperone Hsp33 involved in reactive oxidative species (ROS) metabolism, was required for the suppression of recAts polA lethality at a restricted temperature. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 55 publications
4
18
0
Order By: Relevance
“…In a previous report, we demonstrated that recA polA cells were capable of colony formation in catalase-supplemented media either at a restrictive temperature (42 °C) [ 2 ] or in a rich medium [ 3 ]. Since catalase is a hydrogen peroxide-degrading enzyme, this suggested that the inability of recAts polA cells to grow at restrictive temperatures resulted from hydrogen peroxide accumulation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous report, we demonstrated that recA polA cells were capable of colony formation in catalase-supplemented media either at a restrictive temperature (42 °C) [ 2 ] or in a rich medium [ 3 ]. Since catalase is a hydrogen peroxide-degrading enzyme, this suggested that the inability of recAts polA cells to grow at restrictive temperatures resulted from hydrogen peroxide accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study on recAts polA lethality reported that intracellular ROS accumulation was associated with lethality at the restrictive temperature [ 2 ]. However, why hslO was required to suppress recAts polA lethality was unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations